Comparative metabolite fingerprinting of legumes using LC-MS-based untargeted metabolomics. (December 2019) - Llorach, Rafael; Favari, Claudia; Alonso, David; Garcia-Aloy, Mar; Andres-Lacueva, Cristina; Urpi-Sarda, Mireia
Abstract: Legumes are a well-known source of phytochemicals and are commonly believed to have similar composition between different genera. To date, there are no studies evaluating changes in legumes to discover those compounds that help to discriminate for food quality and authenticity. The aim of this work was to characterize and make a comparative analysis of the composition of bioactive compounds between Cicer arietinum L. (chickpea), Lens culinaris L. (lentil) and Phaseolus vulgaris L. (white bean) through an LC-MS-Orbitrap metabolomic approach to establish which compounds discriminate between the three studied legumes. Untargeted metabolomic analysis was carried out by LC-MS-Orbitrap from extracts of freeze-dried legumes prepared from pre-cooked canned legumes. The metabolomic data treatment and statistical analysis were realized by using MAIT R's package, and final identification and characterization was done using MS n experiments. Fold-change evaluation was made through Metaboanalyst 4.0. Results showed 43 identified and characterized compounds displaying differences between the three legumes. Polyphenols, mainly flavonol and flavanol compounds, were the main group with 30 identified compounds, followed by α-galactosides ( n = 5). Fatty acyls, prenol lipids, a nucleoside and organic compounds were also characterized. The fold-change analysis showed flavanols as the wider class of discriminative compounds of lentils compared to the other legumes; prenol lipids and eucomic acids were the most discriminative compounds of beans versus other legumes and several phenolic acids (such as primeveroside salycilic), kaempferol derivatives, coumesterol and α-galactosides were the most discriminative compounds of chickpeas. This study highlights the applicability of metabolomics for evaluating which are the characteristic compounds of the different legumes. In addition, it describes the future application of metabolomics as tool for the quality control of foods and authentication of different kinds of legumes. Graphical abstract: Unlabelled Image Highlights: LC-MS untargeted metabolomics to compare lentils, beans and chickpeas metabolome. Six classes of compounds were statistically different between evaluated legumes. Flavanol compounds were the most discriminant compounds of lentils. Eucomic acid derivatives and prenol lipids were the most discriminant compounds of beans. Several classes of compounds discriminate chickpeas from the other two legumes.